Thinking Beyond Humanitarian Borders - Ticktin, Miriam (Social research, 2016)
In the language of humanitarianism has played a central role in political and media debates about undocumented migrants/refugees crossing into Europe and North America. The unaccompanied minors entering the US reached the designation of "humanitarian crisis" in the summer of 2014, whereas the tipping point in the Mediterranean came in April 2015, when at least five boats sank and close to 1,200 people drowned en route to Europe. In response to the drownings of 700 people traveling from Libya to Lampedusa, European Union Foreign Policy Commissioner Federica Mogherini stated that "The EU was created on the idea of the protection of human rights, human dignity and human life. They have to be consistent with that idea" (Lyman 2015). In other words, it seems the only subject position available to those who are not trying to build fences or walls is "humanitarian."